Intelligent Agent-Based Collaborative Concept Map Learning - Kuan , Chuen Lee (2005)

(untitled)
This study aims to propose cognitive and sosial scaffolds for learning in 4 ways. The first scaffold is a concept map to externalize students' mental models so that reflection, review and reasons for refinement are overt. The second scaffold is the addition of a collaborative component to the concept map to enable discussion and manipulation of multiple views within a common knowledge workspace. The third scaffold incorporates cognitive apprenticeship models to involve the student in learning as apprentices. Lastly, an agent that provides explanatory system and incremental hinting when requested by the student further complements it.